Influencia de las tics en el aprendizaje basado en proyectos para los estudiantes de noveno año de la Escuela de Educación Básica Víctor Manuel Villamarín, Quinsaloma, 2021-2022 - García Sánchez, Mercedes Teresa (2022)
The present research project was based on determining the influence generated by the use of ICTs in project-based learning in ninth-year students of the Víctor Manuel Villamarín School of Basic Education, belonging to the Quinsaloma canton, which It arises due to the need to verify if the applications of ICTs have a positive influence on project-based learning or, if not, it is unfavorable in the teaching of students, for which the general objective was to demonstrate the influence of ICTs. in the PBL in the ninth year students of the EEB Víctor Manuel Villamarín. The research was based on a population made up of 30 teachers who belong to the institution. The research that was proposed was of an applied type, with a mixed approach and a descriptive and explanatory scope, in order to provide answers to the questions raised. The technique for development was the survey, for which a questionnaire of 18 closed questions with a Licker scale of five alternatives was used. It is concluded through the application of the Spearman correlation that the pertinent strategies positively influence the teaching of the students, satisfying the educational needs that the teachers have at the moment and obtaining tools that help to train the students, for which it will allow to develop a good and effective learning process, as well as obtaining a better long-term retention of information, developing oral and written skills that allow effective communication to help build confidence in student learning, obtaining a good teaching process and effective.